Implementing Cognitive Strategy Instruction to Improve the Actual Intellectual Abilities of the Undergraduate Students with Cognitive Expression Difficulties - Martini Jamaris (Journal of ICSAR, 2019)
This research aims to find out the effectiveness of cognitive strategy instruction for improving intellectual abilities of undergraduate students with cognitive expressing difficulties, especially in actualizing their thinking abilities starting from lower order thinking up to higher order thinking. Therefore, the cognitive strategy instructional design based on Bloom’s Taxonomy is constructed in order to accomplish the research objectives. This research uses mixed method approach entailing the implementation of two research methods. The first is qualitative method which aims to get information of the cognitive strategy in instructional process. The second is quantitative method which is used to measure the students’ improvement in cognitive abilities or actual intellectual abilities after participating in cognitive strategies instruction. Research implementation is divided into three stages. The first stage is needs assessment, in which the students’ thinking / cognitive skill abilities are observed and measured in order to have evidence whether or not they have cognitive expression difficulties. The second stage is to use the needs assessment results in designing cognitive strategy instruction. The third stage is the implementation of the instructional design. There are 20 undergraduate students taking part in this research who are selected by purposive sampling technique. The results revealed that cognitive strategy instruction effectively improves the actual intellectual abilities of students with cognitive expression difficulties. Qualitatively, the students feel very satisfied with their actual intellectual abilities.